Local Cloud Design for Ease of Management and Security of Sensitive Data in Business Organizations - Sekti, Binastya Anggara; Laksana, Ryan Putra; Marwan, Rudi Heri; Laksono, Mohamad Iqbal Ajie; Anwar, Nizirwan (Jurnal Teknologi Informatika dan Komputer, 2025)
The rapid development of information technology makes business organizations face major challenges in managing and securing sensitive data. The development of information technology has changed data storage systems from local media to cloud computing, enabling data access and processing via the internet. Services like Google Drive and OneDrive offer security, accessibility, and data backup, but pose challenges for business organizations, especially in terms of security of sensitive data and operational costs that increase as users grow. This research aims to design a local cloud as a private cloud to improve data management and security in the organization. With a private cloud, companies can control data access more tightly, increase privacy, and enable employees to access applications and data from various locations more safely and efficiently. The results of this research are in the form of a private cloud based on a private server which was developed as a file server with access rights based on departments, across departments, projects or work groups. This system utilizes open-source technology and is equipped with an encrypted Virtual Private Network (VPN) to support remote work models (Work From Home, WFH) and work flexibility from anywhere (Work From Anywhere, WFA). With this solution, organizations can increase operational efficiency, reduce the risk of data leaks, optimize more affordable technology resources, and maintain full control of sensitive company data.